Audiovisual Analysis of the Dahmer Series: Genealogy of a Monster and Family Models - Rafael Hurtado Domínguez; Domínguez Partida, Gabriel; Díaz Cerveró, Elba (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article undertakes an examination of the familial representations within the series Dahmer (2022), which draws from the life and crimes of the eponymous serial killer. Employing a methodology rooted in textual analysis, the study elucidates a discernible bias in the portrayal of the perpetrator's familial unit vis-à-vis those of his victims. The principal inference drawn pertains to the thematic privileging of ostensibly "disadvantaged" familial constructs as the ones most adept at societal integration, juxtaposed against the portrayal of the ostensibly normative liberal American familial paradigm, which becomes the locus for the emergence and proliferation of dysfunctions culminating in the figure of the serial killer under scrutiny within this scholarly endeavour.